Osobennosti vzyaimosvyazi "pul'sovykh rezhimov" i kachestva vypolneniya slozhnokoordinatsionnykh uprazhnenii v khudozhestvennoi gimnastike - Zemskov, E. A.; Kaledina, I. V. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of the study was to analyze the character of heart beats frequency's dynamics when performing the competitive and the specific training loads. It had been revealed that the quality of 720o turns is connected with the running indices of heart beats frequency if the training loads regime is characterized by 175-200 heart beats in a minute.